Performance of Na-ion Supercapacitors Under Non-ambient Conditions—From Temperature to Magnetic Field Dependent Variation in Specific Capacitance - Biswas, Sudipta; Chowdhury, Ananya; Chandra, Amreesh (Frontiers in Materials, 2019)
Single phase NaFePO4 can works as economically viable cathode material for Na-systems similar to LiFePO4–a material that led to the commercialization of Li-ion based energy systems. The reported microstructures of hollow NaFePO4 particles, with porous walls, establish their advantages over solid morphologies. The hollow structures deliver stable electrochemical specific capacitance of 115 F g−1 in 2 M NaOH electrolyte, over a large number of cycles. This observation is directly attributed to the increased surface area, transport channels and redox sites, which become available in the porous-hollow particles. Hitherto unreported electrochemical performance under non-ambient environment is also discussed. In contrast to recently reported in Fe-based metal oxides, where significant change in specific capacitance has been reported as a function of magnetic field, it is observed that NaFePO4 can protect itself and suppress modifications. More importantly, NaFePO4 can work as an efficient electrode material in the temperature range RT to 65°C, which makes it useful for automotive industry.